2021
DOI: 10.1124/dmd.121.000430
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Hepatic and Intestinal Efflux Transport of Statins

Abstract: Previous studies have shown that lipid-lowering statins are transported by various ATP-binding cassette (ABC) transporters. However, due to varying methods, it is difficult to compare the transport profiles of statins. Therefore, we investigated the transport of ten statins or statin metabolites by six ABC transporters using human embryonic kidney cell-derived membrane vesicles. The transporter protein expression levels in the vesicles were quantified with liquid chromatography-tandem mass spectrometry, and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…To determine the regulation of P‐gp by NHERF‐1, CTCs and BeWo cells were treated with rosuvastatin (one of the statin drugs and a substrate to P‐gp) at different points (Figure 3A and 3B). P‐gp transports rosuvastatin in hepatic and intestinal transport systems 39,40 . As anticipated, both CTCs and BeWo cells showed expression patterns similar to NHERF‐1 and P‐gp at different time points after substrate stimulation (Figure 3C and 3D).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…To determine the regulation of P‐gp by NHERF‐1, CTCs and BeWo cells were treated with rosuvastatin (one of the statin drugs and a substrate to P‐gp) at different points (Figure 3A and 3B). P‐gp transports rosuvastatin in hepatic and intestinal transport systems 39,40 . As anticipated, both CTCs and BeWo cells showed expression patterns similar to NHERF‐1 and P‐gp at different time points after substrate stimulation (Figure 3C and 3D).…”
Section: Resultssupporting
confidence: 70%
“…P-gp transports rosuvastatin in hepatic and intestinal transport systems. 39,40 As anticipated, both CTCs and BeWo cells showed expression patterns similar to NHERF-1 and P-gp at different time points after substrate stimulation (Figure 3C and 3D).…”
Section: Expression Of P-gp and Nherf1 In Ctc And Bewo Cells After St...supporting
confidence: 71%
“…[2][3][4][5][6] Some studies have suggested that simvastatin acid is also a substrate of the P-glycoprotein, 13,14 an efflux transporter encoded by the ABCB1 gene, although the evidence is contradictory. 15 Evidence as to the effect of genetic variation in ABCB1 on simvastatin pharmacokinetics is unclear. [16][17][18] As the risk for muscle-related adverse effects increases along with simvastatin exposure, 1,4,5 understanding the genetic variants affecting simvastatin pharmacokinetics is important.…”
Section: Articlementioning
confidence: 99%
“…The SLCO1B1 c.521T>C (p.Val174Ala, rs4149056) missense variant raises simvastatin acid exposure and increases the risk for adverse effects 2–6 . Some studies have suggested that simvastatin acid is also a substrate of the P‐glycoprotein, 13,14 an efflux transporter encoded by the ABCB1 gene, although the evidence is contradictory 15 . Evidence as to the effect of genetic variation in ABCB1 on simvastatin pharmacokinetics is unclear 16–18 …”
mentioning
confidence: 99%
“…Assuming that rosuvastatin CL s,efflux was mediated by passive diffusion only, the predicted CL s,efflux was 19% of the reported PET imaging value (Table 2), which suggests that sinusoidal transporter(s), likely MRP4 (but not MRP3), may be involved in the efflux of rosuvastatin. 13,24,25 Unfortunately, we could not include MRP4-mediated sinusoidal efflux in the REF approach because its abundance was not quantifiable in human liver tissue. 4 In contrast, as expected and discussed below, CL s,efflux was drastically overpredicted by the SCH approach (Table 2).…”
Section: Discussionmentioning
confidence: 99%